Effectiveness and safety of cannabis-based products for medical use in patients with fibromyalgia syndrome: A systematic review - Valentina Lopera; Juan Carlos Restrepo; Pedro Amariles (Elsevier, 2024)
Background: There is a need to explore pharmacological options for syndrome (FMS), such as medical cannabis. The aim of this systematic review was to synthesize and analyze the available information about the effectiveness/efficacy and safety of cannabis-based products for medical use (CBPMs) and cannabis-based medicines (CBMs), in patients with FMS. Methods: Interventional or observational studies, systematic reviews and meta-analysis regarding the effectiveness/efficacy and safety of CBPMs and CBMs in patients with FMS were retrieved from the PubMed/Medline database until April 2024. Then, the information was summarized in tables, with the type of CBPM and CBM, the method used in the study and the effective-ness/efficacy and safety outcomes. Results: 19 publications were selected from the search or form the relevant references. Different CBPM and CBM were used across the studies. Also, different instruments for measuring the effectiveness were used. In general, the use of CBPMs and CBM showed an important improvement in pain, quality of life, and sleep habits. There were no serious adverse events. Conclusions: The results show that CBMPs and CBMs could be effective and safe in patients with FMS; however, the evidence is limited and there is a need for high-quality clinical studies conducted with improved methodological design.